RESPON JENIS DAN DOSIS PEMBERIAN BOKASI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccarata STURT) DALAM POLIBAG - Zulkifli Zulkifli; Putri Lukmana Sari (DINAMIKA PERTANIAN, 2015)
Maize is the most important food commodity containing carbohydrate at the second rank after rice. Organic agriculture is natural farming which is able to suppress the use of organic material giving negative effect on environment. This research aims to examine the response of giving type and dosage of bokasi on growth and yield of Sweet Corn. The completely randomized design was used with 4 x 4 factors. The treatment used four bokasi type namely: weed bokasi (J1), maize bokasi (J2), coconut waste bokasi (J3), and manure bokasi (J4). While, Bokasi dosage consisted of 10 grams per plant (D1), 20 grams per plant (D2), 30 grams per plant (D3), and 40 grams per plant (D4). The parameters observed were cob length, cob diameter, and cob weight per con. The results showed that the best response of giving type and dosage of bokasi was found on weed bokasi under dosage 10 grams per plant with cob length of 13.70 cm, cob diameter of 4.10 cm and cob weight of 95 grams per cob.